2020
DOI: 10.3847/1538-4357/ab88a8
|View full text |Cite
|
Sign up to set email alerts
|

The Dragonfly Wide Field Survey. I. Telescope, Survey Design, and Data Characterization

Abstract: We present a description of the Dragonfly Wide Field Survey (DWFS), a deep photometric survey of a wide area of sky. The DWFS covers 330 deg2 in the equatorial GAMA fields and the Stripe 82 fields in the SDSS g and r bands. It is carried out with the 48-lens Dragonfly Telephoto Array, a telescope that is optimized for the detection of low surface brightness emission. The main goal of the survey is to study the dwarf galaxy population beyond the Local Group. In this paper, we describe the survey design and show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 103 publications
1
48
0
Order By: Relevance
“…While a few deep imaging surveys of the outskirts of local galaxies have recently been completed (e.g. Tal et al 2009;Martínez-Delgado et al 2010;Ludwig et al 2012;Duc et al 2015;Spavone et al 2018) or are ongoing (Danieli et al 2020;Martinez-Delgado et al 2021), the majority of nearby galaxies have not been observed down to the surface brightnesses needed to detect streams from ancient minor mergers.…”
mentioning
confidence: 99%
“…While a few deep imaging surveys of the outskirts of local galaxies have recently been completed (e.g. Tal et al 2009;Martínez-Delgado et al 2010;Ludwig et al 2012;Duc et al 2015;Spavone et al 2018) or are ongoing (Danieli et al 2020;Martinez-Delgado et al 2021), the majority of nearby galaxies have not been observed down to the surface brightnesses needed to detect streams from ancient minor mergers.…”
mentioning
confidence: 99%
“…Indeed, the balances between angular resolution, point-source sensitivity and large-scale features are usually explicit and deliberate choices in astronomical image processing, driven in each case by the particular science goals (e.g. Briggs 1995;Serjeant et al 2003;Smith et al 2019;Danieli et al 2020). One could imagine optimising the loss function not just for completeness or reliability or some balance thereof, but instead to reproduce the sub-mm galaxy source counts, or make the best estimate of the twopoint correlation function of sub-mm galaxies, or reliably detect faint ultra-red sub-mm galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that COSMOS-dw1 was found in a very small and very well-studied field suggests that they may be quite common (as indicated by Klypin et al 2015) and can easily be missed. Low surface brightness-optimized surveys, such as the HSC-SSP (Aihara et al 2018) and the Dragonfly Wide Field Survey (Danieli et al 2020), will provide an additional avenue to obtaining a census of isolated low mass quiescent galaxies.…”
Section: Discussionmentioning
confidence: 99%